Critical success factors in managing global supply chains. (15th May 2008) - Chan, Felix T.S.; Chan, H.K.; Lau, Henry C.W.; Ip, Ralph W.L.
Since the last decade, effective supply chain management has been regarded as the source of cost reduction, improvement of services, and gaining competitive advantages. Some researchers have already investigated several methods that could be employed to manage supply chains as well. However, not all companies can afford to implement all these methods properly. It is because these methods may not be suitable to every company or industry, and it would take a great effort (i.e. money) in doing so. This paper aims to highlight some critical success factors for managing global supply chains, which are obtained by analysis of case studies and related survey results in the literature. The focus of this paper would be put on the vendors' management side. It includes how to select vendors in lean and mass productions, the skills of developing and maintaining relationship by using product development and strategic suppliers' alliance. Suggestions will be given based on the evaluation of the cases and reported literature.